MYCN is an immunosuppressive oncogene dampening the expression of ligands for NK-cell-activating receptors in human high-risk neuroblastoma. (3rd June 2017) - Brandetti, Elisa; Veneziani, Irene; Melaiu, Ombretta; Pezzolo, Annalisa; Castellano, Aurora; Boldrini, Renata; Ferretti, Elisa; Fruci, Doriana; Moretta, Lorenzo; Pistoia, Vito; Locatelli, Franco; Cifaldi, Loredana
ABSTRACT: Neuroblastoma (NB) is the most common extracranial solid tumor occurring in childhood. Amplification of the MYCN oncogene is associated with poor prognosis. Downregulation on NB cells of ligands recognized by Natural Killer (NK) cell-activating receptors, involved in tumor cell recognition and lysis, may contribute to tumor progression and relapse. Here, we demonstrate that in human NB cell lines MYCN expression inversely correlates with that of ligands recognized by NKG2D and DNAM1 activating receptors in human NB cell lines. In the MYCN-inducible Tet-21/N cell line, downregulation of MYCN resulted in enhanced expression of the activating ligands MICA, ULBPs and PVR, which rendered tumor cells more susceptible to recognition and lysis mediated by NK cells. Conversely, a MYCN non-amplified NB cell line transfected with MYCN showed an opposite behavior compared with control cells. Consistent with these findings, an inverse correlation was detected between the expression of MYCN and that of ligands for NK-cell-activating receptors in 12 NB patient specimens both at mRNA and protein levels. Taken together, these results provide the first demonstration that MYCN acts as an immunosuppressive oncogene in NB cells that negatively regulates the expression of ligands for NKG2D and DNAM-1 NK-cell-activating receptors. Our study provides a clue to exploit MYCN expression levels as a biomarker to predict the efficacy of NK-cell-based immunotherapy in NB patients.